Effects of Lactobacillus paracasei LK01 on production performance, egg quality, antioxidant capacity, immunity and intestinal health of laying hens - Wu, Tianjun; Liu, Weixin; Yin, Xinyu; Zhang, Linkun; Chen, Hong; Zhang, Ye; Zhang, Cheng; Jiang, Runsheng; Ding, Xiaoling (Frontiers in Veterinary Science, 2026)
This study aimed to evaluate the effects of dietary supplementation with Lactobacillus paracasei LK01 on production performance, egg quality, serum biochemical parameters, antioxidant capacity, inflammatory factors, intestinal digestive enzyme activities, and cecal microbiota in laying hens, while determining the optimal supplementation level. A total of 288 healthy 20-week-old Jinghong No. 1 laying hens, with uniform body weight and similar egg production rates, were stratified-randomly assigned to four groups (4 replicates/group, 18 hens/replicate): the control group (CON; basal diet) and the low-level (LLP), medium-level (MLP), and high-level (HLP) groups, which received the basal diet supplemented with 10⁶, 107, and 108 CFU/kg of L. paracasei LK01, respectively. The trial included a 1-week adaptation period followed by an 8-week experimental period. Results indicated: (1) L. paracasei LK01 supplementation increased average egg weight and significantly enhanced egg production rates in the MLP and HLP groups compared to the CON group (p < 0.05); (2) The HLP group exhibited increased albumen height and Haugh units, while the LLP group showed improved eggshell strength (p < 0.05); (3) Total protein (TP) levels were elevated in all supplemented groups (p < 0.05), with albumin (ALB) levels increased in the LLP and MLP groups, and total cholesterol (TC) and triglyceride (TG) levels decreased (p < 0.05); (4) Total antioxidant capacity (T-AOC) was enhanced in all supplemented groups, and serum IL-6 and TNF-α levels were reduced in the HLP group (p < 0.05); (5) No significant differences were observed in intestinal digestive enzyme activities (duodenum, jejunum, ileum) between groups (p > 0.05); At the phylum level, the abundance of Spirochaetota was decreased in all supplemented groups (p < 0.05), with Bacteroidetes and Firmicutes remaining the dominant phyla. At the genus level, the abundances of Fusobacterium and Treponema were reduced in all supplemented groups (p < 0.05). In conclusion, dietary L. paracasei LK01 improved laying hen performance, egg quality, serum biochemical parameters, antioxidant capacity, and reduced pro-inflammatory factors while suppressing harmful gut microbiota. The 108 CFU/kg dose appeared optimal based on results; However, as this was the highest concentration tested, further research is needed to confirm the precise optimal level.